HOW PLAY FOSTERS CO-CREATION FOR DESIGN-LED INNOVATION - Jhangiani, Avinash Gautam (Global journal of Business and Integral Security, 2022)
To navigate the increasingly uncertain business environment, human-centric design and innovation is becoming a necessity. The ability to think creatively and come up with new solutions is needed to thrive in the future. This requires a shift of mindset from scalable efficiency of the industrial age to sustainable creativity of the digital age for corporate India. While change is hard, it need not be painful. What if there was a more intrinsically motivating and nourishing way to deal with change? This thesis explores the potential of play as a catalyst of co-creation for design-led innovation in organizations struggling to accelerate transformation. First, through the qualitative, interpretative research method, the practical implications of infusing play into work for serious organizational outcomes are discussed using four single case studies that cover empathy, vulnerability, divergent thinking, and creative agility – four integral skills for managers and leaders to rehumanize business, build creative confidence and accelerate change using the human- vi centric design process. Second, through the cross-case content analysis, this paper quantitatively identifies key micro-behavioral patterns discovered in the co-creation of play-enabled, design-led innovative solutions from six case studies, that result in building design thinking mindsets. Lastly, the within-case and cross-case analysis are compiled and structured to build a conceptual model of skills, behaviors and mindsets resulting from play-infused co-creation, and key implications are provided for organizations struggling to shift mindset and accelerate innovation in the post-pandemic world.